PELAKSANAAN TUGAS LAUNDRY SECTION DI HOUSEKEEPING DEPARTMENT THE ZURI HOTEL DUMAI - Nurul Fadillah; Mariaty Ibrahim (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2023)
ABSTRACT Execution of tasks is a way or steps so that the implementation of work is easy and smooth. In a hotel it is very important to pay attention to the processor for carrying out the laundry section tasks that will be carried out. This study aims to find out how important the attention of hotel management is in carrying out laundry section duties, SOP for washing and servicing hotel guest clothes aand guest clothing services taken from sources processed by the author (2022) in the laundry section housekeeping department The Zuri Hotel Dumai. Data collected using interview techniques, observation and documentation. Based on the research, it was found from the interview results that the implementation of the laundry section duties in the housekeeping department at The Zuri Hotel Dumai can be said to be quite good because there are still those who do not or are not in accordance with predetermined procedures. Keywords: Execution Of Tasks, Laundry Section, Housekeeping Department, The Zuri Hotel Dumai